2021
DOI: 10.21608/ijma.2021.55609.1234
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Effect of Mode of Delivery on Sexual Function: A cross-Sectional Study

Abstract: Background: Female sexual dysfunction [FSD] is a significant challenge. Some researchers reported an association between FSD and delivery mode, while others did not report such association. Aim of the work:To study the long-term effect of delivery mode on female sexual function in primiparous mothers. Subjects and Methods: This is a cross-sectional analytical study conducted to study sexual dysfunction and its related factors after delivery. It included 260 primiparous mothers who attended the healthcare cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, early resumption of sexual activity may increase the risk of postpartum sexual dysfunction and unintended pregnancy [ 49 ]. Similarly, parity has affected women’s early resumption of sexual intercourse; primiparous women are more likely to have an early resumption of sexual intercourse among postpartum women than multiparous women [ 50 ]. We found that women with primipara were 2.88 times more likely to engage in early sexual intercourse during the postpartum period than those multipara women (AOR = 2.88, 95%CI = 1.41, 5.89).…”
Section: Discussionmentioning
confidence: 99%
“…However, early resumption of sexual activity may increase the risk of postpartum sexual dysfunction and unintended pregnancy [ 49 ]. Similarly, parity has affected women’s early resumption of sexual intercourse; primiparous women are more likely to have an early resumption of sexual intercourse among postpartum women than multiparous women [ 50 ]. We found that women with primipara were 2.88 times more likely to engage in early sexual intercourse during the postpartum period than those multipara women (AOR = 2.88, 95%CI = 1.41, 5.89).…”
Section: Discussionmentioning
confidence: 99%